Three months of weekly rifapentine plus isoniazid for TB prevention among people with HIV - R. Borse; B. Randive; S. Mattoo; P. Malik; H. Solanki; A. Gupta; R.E. Chaisson; V. Mave; N. Suryavanshi (IJTLD Open)
BACKGROUND: Evidence on implementation of three months of weekly isoniazid (H, INH) and rifapentine (P, RPT) (3HP) as a TB preventive therapy (TPT) for at-risk groups in Indian programmatic conditions is limited. METHODS: A prospective demonstration study assessing scale-up, safety, and effectiveness of 3HP TPT among people living with HIV (PLHIV) in Indian programmatic settings was conducted. RESULTS: Of 656 screened PLHIV, 502 (77%) received 3HP. Of these, 20 (4%) discontinued TPT due to toxicity,17 (3.8%) lost to follow-up, one (0.2%) had breakthrough rifampicin-sensitive TB, and 464 (92%) completed 3 HP TPT. Of 288 (57%) overall adverse events (AEs), 46 (9%) had Grade 2 or above AEs. The median time to AE was 14 days (IQR 7–42). Serious adverse events (SAEs) were reported in 9 (2%) participants; of these, 7 (78%) were not related to 3HP. No TB episodes occurred during the 1-year follow-up period. CONCLUSION: 3HP TPT completion rate of 92%, with few adverse events leading to 3HP discontinuation, providing evidence of the scalability and safety of 3HP TPT among PLHIV in Indian health program settings.